Qaulan Sadida in the Perspective of the Qur'an and Hadith as Communication Ethics in the Post-Truth Era of Social Media - Arifatusshofwah, Pratmadhieta; Shohib, Muhammad Wildan (Universitas Muhammadiyah Surakarta, 2025)
This study aims to reconstruct the concept of Qaulan Sadida as the foundation of Islamic communication ethics in facing the post-truth phenomenon and to analyze its implementation in Islamic Religious Education materials to shape students' digital literacy. The method used is a qualitative approach through literature study with primary data sources in the form of Tafsir Al-Mishbah by M. Quraish Shihab, the book Pendidikan Agama Islam dan Budi Pekerti (Islamic Religious Education and Morality), and Post-Truth by Lee McIntyre, supported by various relevant scientific journals. Data analysis was conducted using the Miles and Huberman model through the stages of reduction, presentation, and conclusion drawing. The results of the study show that Qaulan Sadida does not only mean speaking the truth literally, but also includes accuracy, factual honesty, and moral responsibility in communication. The reconstruction of this value is relevant in the face of a post-truth culture that blurs the line between fact and opinion. The integration of Qaulan Sadida into teaching materials has the potential to strengthen students' digital literacy through the habit of critical thinking, the practice of tabayyun, and the application of polite and responsible media ethics. In practical terms, these findings provide a conceptual basis for the development of learning materials and strategies that are contextualized to the digital reality. The values of Qaulan Sadida can be operationalized as a framework for ethical communication in cyberspace, thereby not only equipping students with technical skills, but also shaping their digital character. The contribution of this research lies in strengthening the integration of Qur'anic values in digital literacy to produce a generation of Muslims who are critical, polite, and empowered to break the chain of disinformation in the post truth era.